2008
DOI: 10.1371/journal.pbio.0060110
|View full text |Cite
|
Sign up to set email alerts
|

The Parasexual Cycle in Candida albicans Provides an Alternative Pathway to Meiosis for the Formation of Recombinant Strains

Abstract: Candida albicans has an elaborate, yet efficient, mating system that promotes conjugation between diploid a and α strains. The product of mating is a tetraploid a/α cell that must undergo a reductional division to return to the diploid state. Despite the presence of several “meiosis-specific” genes in the C. albicans genome, a meiotic program has not been observed. Instead, tetraploid products of mating can be induced to undergo efficient, random chromosome loss, often producing strains that are diploid, or cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
377
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 300 publications
(401 citation statements)
references
References 73 publications
16
377
2
1
Order By: Relevance
“…5). However, we cannot rule out that other forms of recombination occur in bdelloid populations in ways that do not require homologous pairing, such as parasexuality 26 . The high number of horizontally acquired genes, including some seemingly recent ones, suggests that HGTs may also be occurring from rotifer to rotifer.…”
Section: Letter Researchmentioning
confidence: 97%
“…5). However, we cannot rule out that other forms of recombination occur in bdelloid populations in ways that do not require homologous pairing, such as parasexuality 26 . The high number of horizontally acquired genes, including some seemingly recent ones, suggests that HGTs may also be occurring from rotifer to rotifer.…”
Section: Letter Researchmentioning
confidence: 97%
“…To further analyze a potential relationship between growth rates and white-opaque switching, we tested progeny from the parasexual cycle of C. albicans for their doubling times and switching frequencies. Sexual reproduction in C. albicans occurs between opaque a and ␣ cells and is completed by an unusual mechanism of chromosome loss in tetraploid strains, generating recombinant diploid and aneuploid products (Bennett and Johnson, 2003;Forche et al, 2008). Previous studies demonstrated that many of the progeny derived from the parasexual cycle were slower growing than parental SC5314 strains, even in progeny with a euploid complement of chromosomes (Forche et al, 2008).…”
Section: A Connection Between White-opaque Switching and Cellular Gromentioning
confidence: 99%
“…Sexual reproduction in C. albicans occurs between opaque a and ␣ cells and is completed by an unusual mechanism of chromosome loss in tetraploid strains, generating recombinant diploid and aneuploid products (Bennett and Johnson, 2003;Forche et al, 2008). Previous studies demonstrated that many of the progeny derived from the parasexual cycle were slower growing than parental SC5314 strains, even in progeny with a euploid complement of chromosomes (Forche et al, 2008). Analysis of euploid progeny identified several slow-growing diploid strains that also underwent switching at high frequency (e.g., isolates P6 and Ss10; Table 4).…”
Section: A Connection Between White-opaque Switching and Cellular Gromentioning
confidence: 99%
“…Although C. albicans is typically isolated as a diploid, it is also capable of propagating in the haploid or tetraploid states [22,40]. Furthermore, as noted above, aneuploid cells carrying an abnormal complement of chromosomes are frequently found among clinical C. albicans strains [11,[41][42][43], suggesting they can provide a selective advantage in some host contexts.…”
Section: Genomic Architecturementioning
confidence: 99%
“…However, MLST karyotyping relied on genetic information at a limited number of loci, which may have obfuscated identification of hybrid strains or introgressed genomic regions resulting from sexual exchange [22].…”
mentioning
confidence: 99%